Conspirituality : how new age conspiracy theories became a health threat - Beres, Derek; Remski, Matthew D., 1971-; Walker, Julian (Podcaster) (PublicAffairs, 2023)
"Conspirituality takes a deep dive into the troubling phenomenon of influencers who have curdled New Age spirituality and wellness with the politics of paranoia--peddling vaccine misinformation, tales of child trafficking, and wild conspiracy theories. In the early days of the COVID-19 pandemic, a disturbing social media trend emerged: a large number of yoga instructors and alt-health influencers were posting stories about a secretive global cabal bent on controlling the world's population with a genocidal vaccine. Instagram feeds that had been serving up green smoothie recipes and Mary Oliver poems became firehoses of Fox News links, memes from 4chan, and prophecies of global transformation. Since May 2020, Derek Beres, Matthew Remski and Julian Walker have used their Conspirituality podcast to expose countless facets of the intersection of alt-health practitioners with far-right conspiracy trolls. Now this expansive and revelatory book unpacks the follies, frauds, cons and cults that dominate the New Age and wellness spheres and betray the trust of people who seek genuine relief in this uncertain age. With analytical rigor and irreverent humor, Conspirituality offers an antidote to our times, helping readers recognize wellness grifts, engage with loved ones who've fallen under the influence, and counter lies and distortions with insight and empathy."--Publisher.